LINGUISTIC PERFORMANCE OF FORMER US PRESIDENT OVER DEVELOPING TERRORISM IN THE MIDDLE EAST - Mostafa Shahiditabar; Mohammad Amin Mozaheb; Mohsen Mohseni; Abolfazl Babaei; Amir Hossein Rashidi; Ali Dehchali; Mojtaba Hosseini; Hossein Pourghasemian (Universitas Kuningan, 2017)
This study aims to reveal how a single reality, i.e., terrorism, is presented and viewed by US officials. The corpus of the current study is US President Barack Obamas speeches from 2011 to 2015. The approach used in this study to detect discursive structures within the transcripts of the American officials speeches and discover the ideologies underlying them is Van Dijks (2004) as well as a content-based analysis method. As far as the analysis the data is concerned, the macro strategies of positive self-representation and negative other- representation are useful to evaluate attitudes and opinions on the one hand, that is, Obama has applied polarization, victimization, actor description, national self-glorification, presupposition, lexicalization, and actor description among other strategies in his speeches. On the other hand, the findings prove that Obamas impressions of terrorism versus terrorists and states versus people are changing from 2011 to 2015. The findings of the present study is hoped to be useful for both critical discourse analysts and political activists.